Reflection on theteaching practice (Nóema, 2016)
According Klemperer language thinks for us. But also the institutions think for us. With the result that the practices often determine a common thought that is shared and made their own without realizing it. What thought communicates the current organization of the teaching practice of the Italian schools? The report answers this question by showing how users should be aware of the precise meaning of these educational practices.
Keywords: educational practices; pedagogy; Klemperer; school